Social-ecological correlates of accelerometer-measured occupational sitting among Japanese desk-based workers - Satoshi Kurita; Ai Shibata; Kaori Ishii; Mohammad Javad Koohsari; Koichiro Oka (BMC, 2019)
Abstract Background Although the main targets for reducing workplace sedentary behavior have been clarified, only a few studies have examined the association between social-ecological factors and workplace sedentary behavior for effective intervention. The present study aimed to examine the social-ecological factors of workplace sedentary behavior among Japanese sedentary workers. Methods Participants were recruited via a cross-sectional mail survey targeting randomly sampled 6000 middle-aged people dwelling in Matsuyama-city and Koto-ku in Japan. Participants answered a questionnaire on social-ecological factors, recorded their work time in a diary, and wore a triaxial accelerometer during waking time for 7 consecutive days. Workplace sedentary behavior was measured using accelerometer and was referred to as the work time in the recorded diary. Full-time workers who had mainly sitting work and valid accelerometer data were included in the analysis. Workplace sedentary variables were sedentary breaks per sedentary hour, sedentary time, and ≥ 30 min bouts of sedentary time. The associations between each sedentary variable and social-ecological factors were explored by conducting three multiple linear regression analyses adjusting for sociodemographic and health-related factors. Results A total of 227 participants (133 men, mean age 49.9 ± 6.9 years) were included in the analysis. In the overall sample, "typically seeing work colleagues take sedentary breaks" was significantly associated with more sedentary breaks (B [95% confidence interval CI=1.40 [0.07 to 2.73]) and shorter ≥30-min bouts of sedentary time (B [95% CI] = −7.08 [−13.75 to −0.40]). "I am motivated to take sedentary breaks" had an unfavorable association with less sedentary breaks (B [95% CI] = −1.36 [−2.61 to −0.12]) and longer sedentary time (B [95% CI] = 4.15 [0.29 to 8.00]). In male workers, "Too stressed to take sedentary breaks" was significantly associated with less sedentary breaks (B [95% CI] = −5.6 [−9.17 to −2.02]). Conclusions Seeing work colleagues take sedentary breaks may be important for reducing workplace sedentary behavior. Those who are more sedentary are motivated to take sedentary breaks. Male workers who feel the need to take sedentary breaks at work are more sedentary.